Sedimentology and sedimentary basins from turbulence to tectonics - Leeder, M. R. (Mike R.) (Chichester, West Sussex, UK Hoboken, NJ Wiley-Blackwell, 2011)
The sedimentary record on Earth stretches back more than 4.3 billion years and is present in more abbreviated forms on companion planets of the Solar System, like Mars and Venus, and doubtless elsewhere. Reading such planetary archives correctly requires intimate knowledge of modern sedimentary processes acting within the framework provided by tectonics, climate and sea or lake level variations. The subject of sedimentology thus encompasses the origins, transport and deposition of mineral sediment on planetary surfaces. The author addresses the principles of the subject from the viewpoint of modern processes, emphasising a general science narrative approach in the main text, with quantitative background derived in enabling 'cookie' appendices. The book ends with an innovative chapter dealing with how sedimentology is currently informing a variety of cognate disciplines, from the timing and extent tectonic uplift to variations in palaeoclimate. Each chapter concludes with a detailed guide to key further reading leading to a large bibliography of over 2500 entries. The book is designed to reach an audience of senior undergraduate and graduate students and interested academic and industry professionals.
The sedimentary record on Earth stretches back more than 4.3 billion years and is present in more abbreviated forms on companion planets of the Solar System, like Mars and Venus, and doubtless elsewhere
Machine generated contents note: Contents list will be adapted from contents of current edition based on recommendations of reviewers.
Machine generated contents note: Contents list will be adapted from contents of current edition based on recommendations of reviewers.
Includes bibliographical references and index.
Keywords: Sedimentology; Sedimentary basins